Voltage Gated Calcium Channel Activation by Backpropagating Action Potentials Downregulates NMDAR Function - Theis, Anne-Kathrin; Rózsa, Balázs; Katona, Gergely; Schmitz, Dietmar; Johenning, Friedrich W. (Frontiers in Cellular Neuroscience, 2018)
The majority of excitatory synapses are located on dendritic spines of cortical glutamatergic neurons. In spines, compartmentalized Ca2+ signals transduce electrical activity into specific long-term biochemical and structural changes. Action potentials (APs) propagate back into the dendritic tree and activate voltage gated Ca2+ channels (VGCCs). For spines, this global mode of spine Ca2+ signaling is a direct biochemical feedback of suprathreshold neuronal activity. We previously demonstrated that backpropagating APs (bAPs) result in long-term enhancement of spine VGCCs. This activity-dependent VGCC plasticity results in a large interspine variability of VGCC Ca2+ influx. Here, we investigate how spine VGCCs affect glutamatergic synaptic transmission. We combined electrophysiology, two-photon Ca2+ imaging and two-photon glutamate uncaging in acute brain slices from rats. T- and R- type VGCCs were the dominant depolarization-associated Ca2+conductances in dendritic spines of excitatory layer 2 neurons and do not affect synaptic EPSPs measured at the soma. Using two-photon glutamate uncaging, we compared the properties of glutamatergic synapses of single spines that express different levels of VGCCs. While VGCCs contributed to EPSP mediated Ca2+ influx, the amount of EPSP mediated Ca2+ influx is not determined by spine VGCC expression. On a longer timescale, the activation of VGCCs by backpropagating AP bursts results in downregulation of spine NMDAR function.